SETTLEMENT OF SEXUAL VIOLENCE AGAINST CHILDREN BASED ON BALINESE CUSTOMARY LAW - Gede Rhama Sukmayoga Wiweka; Anak Agung Istri Ari Atu Dewi; Putu Gede Arya Sumertayasa; I Nyoman Bagiastra (Transpublika Publisher, 2024)
This study aims to examine and analyze related to the settlement of crimes of sexual violence against children based on positive law in Indonesia and Balinese customary law. This study uses normative legal research methods with factual approaches, statutory approaches, case approaches, and legal concept analysis approaches. The results of this study explain that arrangements related to sexual violence against children are regulated in Article 81 and Article 82 of the UUPA, regarding their settlement according to the criminal justice system according to the provisions of the Criminal Procedure Code. As well as the settlement of criminal acts of sexual violence against children in Balinese customary law is translated into two approaches to justice, namely criminal sanctions with a retributive approach or criminal sanctions with a restorative approach. And if the settlement is through a restorative approach, the rights of the victim need attention because the victim is an interested party who should have a (legal) position in the settlement process. However, in the criminal justice system in general, it is suspected that victims do not receive equal protection from the authorities in the criminal justice system, so that the true interests of victims are often neglected and even if they do exist, they are only fulfilling the criminal justice administration or management system.